Dynamic walking simulation and balancing characterization of a fuzzy-controlled penta-limbed biped robot - Monje, Jose Claro N. (1997)
The mathematical dynamic model of a single support leg penta-limb biped robot is complicated to use and solve in a conventional control system. Not only is it multivariable, but it also involves simultaneous variable-coefficient second-order nonlinear differential equations that may not yield closed form equations and thus be unsolvable. A fuzzy controller, on the other hand, can make the robot walk forward or stop and balance itself. The fuzzy controller can decide on the robot's next movement without using any mathematical model, and thus avoid the complication of having to solve control system equations. This thesis proposal aims to demonstrate this by simulation of the robot's walking and stopping movement.